Pengendalian Diri Pada Penderita OCD - Salamah, Sherlia Nailus; Muámmaroh, Nurul Lail Rosyidatul (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2021)
Self-control is the ability to control / hold or limit one's emotions and behavior. Whereas OCD is synonymous with sedentary thoughts and repeated repetitive behavior. So that self-control can help people with OCD in carrying out daily activities. This study aims to determine how self-control in patients with Obsessive Compulsive Disorder (OCD). The subjects in this study were three people. Because of the specifics of the subject, the researchers used a qualitative method with a case study approach. The instruments in this study used passive participation observation, semi-structured interviews and documentation studies. The results of this study indicate that differences in the characteristics of OCD sufferers experienced lead to different behavior and self-control. And every self-control can be categorized into several aspects of self-control. As for the three aspects of self control that are commonly carried out by the subject are behavioral control aspects. Where the subjects in this study, are better able to control the disturbance by modifying an unpleasant situation into something that can still be done. This also relates to the level of intelligence above the average of each subject at the time of examination.